Moving Towards a More Dynamic Business Sector in Spain - González Pandiella, Alberto (OECD Economics Department Working Papers, 2014)
Policy efforts to revitalise entrepreneurship and investment in Spain are key to generating growth and new jobs. The government has a substantial reform program to make it easier to do business in Spain, which should in some cases be deepened. Boosting economic growth requires a new generation of high-growth companies and that resources flow towards the most productive firms. For this to happen, barriers to business growth have to be reduced by streamlining regulations and licencing procedures, internationalisation needs to be fostered, and competition strengthened. In addition, the negative impact of the crisis on companies, notably the high level of indebtedness and difficulties to obtain financing faced by some firms has to be relieved. This would be facilitated by more efficient insolvency procedures and further development of non-bank financing